2022
DOI: 10.1164/rccm.202109-2163oc
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Oxygen for Severe Hypoxemia: Oxygenation Response and Outcome in Patients with COVID-19

Abstract: At a Glance CommentaryScientific Knowledge on the Subject: In order to identify patients in the initial stages of ARDS, and facilitate inclusion into clinical trials aimed at earlier treatment, several studies have suggested diagnosing ARDS in the patients not receiving mechanical ventilation.However, the oxygenation criterion of the Berlin definition states that for the diagnosis of moderate or severe ARDS, a patient must be on invasive mechanical ventilation with a PEEP > 5 cmH 2 O, when the PaO2/FiO2 is mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
(62 reference statements)
2
39
0
Order By: Relevance
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and evaluating the full texts of articles, we identified 23 eligible studies 9 , 11 32 (3 RCTs, 20 , 24 , 26 8 prospective observational studies, 13 , 16 , 18 , 19 , 22 , 25 , 28 , 30 and 12 retrospective observational studies). 9 , 11 , 12 , 14 , 15 , 17 , 21 , 23 , 27 , 29 , 31 , 32 The process of searching and screening is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were considered to have an unclear risk of bias. The 20 observational 9 , 11 19 , 21 23 , 25 , 27 32 studies were assessed using the NOS checklist, and the results are shown in the Table 2 . All studies were of medium quality (⩾5 stars) or above, and 10 were considered high quality (⩾8 stars).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite lacking clinical evidence, ARDS criteria have been applied to patients not undergoing invasive mechanical ventilation [ 9 ]. Recent reports have indicated some applicability of a low PaO 2 /F I O 2 ratio during HFNC to predict mortality [ 10 ]. The main aim of the current study was to allow the accurate stratification of respiratory dysfunction during HFNC and NIV in COVID-19 ARDS patients by providing expected differences in PaO 2 /F I O 2 ratio upon a change in ventilatory strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Journal , Ranieri and colleagues (pp. 431–439 ) provide new data to help inform this discussion ( 13 ). Ranieri and colleagues analyzed outcomes of patients with COVID-19 pneumonia from four Italian studies, including three observational and one interventional study.…”
mentioning
confidence: 99%